Micromixing assessment of confined impinging jet mixers used in RIM - Nunes, Maria I. (2019)
The simultaneous azo couplings of 1- and 2-naphthols with diazotized sulfanilic acid have been widely used to study the influence of mixing on the product distribution of fast chemical reactions with fluids of low viscosities. The aim of this work is to assess the micromixing performance of the mixing chamber of a RIM (Reaction Injection Molding) machine, when high viscosity fluids are used. The mixing characterization study in the RIM machine has shown that an increase of Reynolds number, over a very short range, 100<Re<400, enhances significantly the micromixing intensity inside the mixing chamber. The transition from a fully segregated regime to the self-sustainable chaotic flow, at Reynolds number values of 100–125, was also observed. Furthermore, it is shown that the iso-momentum condition between the opposed jets in RIM is fundamental to ensure the continuous presence of a self-sustainable chaotic flow regime, at which the best mixing conditions are obtained.